Teachers' beliefs and classroom practices on the use of video in English language teaching - Budi Waluyo; Aisah Apridayani (Studies in English Language and Education, 2021)
In the last decade, there has been a growing interest in exploring why teachers decide to and not to use a technological tool in their teaching practices. Teachers’ beliefs have appeared to be one of the influential factors, yet still little is known about what causes both consistencies and inconsistencies between teachers’ beliefs and their classroom practices, especially on the use of technology. Thus, to address such a gap, this study examined teachers’ beliefs about video and their use of video in English Language Teaching (ELT) along with the key factors causing the inconsistencies between teachers’ pedagogical beliefs about video and their classroom practices. A qualitative research design with semi-structured interviews involving English teachers at a private educational institution in Indonesia was employed. The collected data were analyzed by using individual topic codes and emerging themes. The findings revealed that teachers’ beliefs about the use of video in ELT were positive but inconsistent with their use of video in practices. Four key factors underlying the inconsistencies between teachers’ pedagogical beliefs about video and their use of video in classroom teaching were identified, which involved teaching philosophy, teacher’s knowledge and skill, facility, and reading literature. Therefore, pedagogically, the findings implicate that teachers’ beliefs and classroom practices can be bridged by addressing the four underlying factors.